Merdeka Belajar Innovation Through Strengthening Competition Of Islamic Higher Education In Society Era 5.0 - Tubagus Syihabudin; Ilzamudin Ma’mur; Rijal Firdaos (Paedagogia: Jurnal Pendidikan, 2023)
The disruption era creates a social arrangement of life that adapts to the conditions and goals set. Indonesia, a Muslim majority, must be adjusted by educational innovations, namely independent learning. Adaptation and adoption are a necessity. Islamic higher education must be reformulated, characterised by a balance of human behaviour and the role of technology in education. The study explores how Islamic higher education can compete in society era 5.0. The results show that Merdeka Belajar innovation is carried out by developing in harmony with Merdeka Belajar curricula and multilevel learning innovations. While strengthening Islamic higher education is based on aqidah sohihah, philosophy, five senses, intuition, character, rationality, and authority as a source of knowledge, all of which must be used as an inspirational approach. The competitive advantage of Islamic higher education needs leadership skills and human resources, teamwork differentiation, cooperation network, service quality differentiation, financial innovation, religious culture, and quality culture. The research implies that the better the independent learning innovation, the more vital Islamic higher education through multifunctional, adaptive, and flexible learning with the highest level of competitive quality creates Islamic education that can be applied in society era 5.0